2010
DOI: 10.1074/jbc.m109.068726
|View full text |Cite
|
Sign up to set email alerts
|

Location of 3-Hydroxyproline Residues in Collagen Types I, II, III, and V/XI Implies a Role in Fibril Supramolecular Assembly

Abstract: Collagen triple helices are stabilized by 4-hydroxyproline residues. No function is known for the much less common 3-hydroxyproline (3Hyp), although genetic defects inhibiting its formation cause recessive osteogenesis imperfecta. To help understand the pathogenesis, we used mass spectrometry to identify the sites and local sequence motifs of 3Hyp residues in fibril-forming collagens from normal human and bovine tissues. The results confirm a single, essentially fully occupied 3Hyp site (A1) at Pro 986 in A-cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
189
3
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(218 citation statements)
references
References 50 publications
16
189
3
4
Order By: Relevance
“…Hyp occurs exclusively at position y (Fietzek and Rauterberg 1975), recent studies showed that Hyp also occurs at position x in fibrillar collagens (Song and Mechref 2013;Weis et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Hyp occurs exclusively at position y (Fietzek and Rauterberg 1975), recent studies showed that Hyp also occurs at position x in fibrillar collagens (Song and Mechref 2013;Weis et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…During this phase, 65 kDa FK506 binding protein (FKBP65; encoded by FKBP10) and a complex formed by P3H1 -CRTAPPPIase B (peptidyl prolyl cis-trans isomerase B) -seem to play a crucial part. The complex is involved in the hydroxyl ation of proline 986 of the collagen α1(I) chain and α1(II) chain and proline 707 of the α2(I) chain 13,[19][20][21] , which are thought to be important for supramolecular assembly of collagen fibrils and to serve as binding sites for chaperones or small leucine rich proteoglycans 22 . Beyond its prolyl 3 hydroxylase activity, the com plex functions as a PPIase and chaperone for collagen folding 13,19,23 .…”
Section: Mechanisms/pathophysiologymentioning
confidence: 99%
“…Red, hydroxylated, non-glycosylated residues; green, Glc-Gal-Hyl residues; dark blue, Gal-Hyl residue; purple, residue found as both Glc-Gal-Hyl and Gal-Hyl. Underlined, hydroxylated/glycosylated residues mapped in previous studies (4,32). Sequences not identified in the course of MS analysis are in light blue.…”
Section: Hydroxylated Residues and Glycosylated Hyl Residues Of Humanmentioning
confidence: 99%
“…Recent analyses of collagenous proteins by MS relied heavily on a priori biological knowledge to assess prolyl hydroxylation (i.e. PTM assignment based upon hydroxylation motifs) (30,32) rather than PTM assignment based upon localizing fragments from MS n spectra. We report comprehensive mapping of all PTMs involving hydroxylated residues on bovine placenta ␣1(V) and human recombinant pro-␣1(V) collagen chains and provide manually verified mass spectral evidence for each modified site.…”
Section: Collagen Type V (Col(v))mentioning
confidence: 99%